Comparative Encapsulation Efficiency of Lutein in Micelles Synthesized via Batch and High Throughput Methods - Cosby LE (Dove Medical Press, 2020)
Lauren E Cosby,1 Kil Ho Lee,2 Thomas J Knobloch,3 Christopher M Weghorst,3 Jessica O Winter1,2 1Biomedical Engineering, The Ohio State University, Columbus, OH 43210, USA; 2William G. Lowrie Department of Chemical and Biomolecular Engineering, The Ohio State University, Columbus, OH 43210, USA; 3College of Public Health, Division of Environmental Health Sciences, The Ohio State University, Columbus, OH 43210, USACorrespondence: Jessica O Winter Tel +1 614 247 7668Email winter.63@osu.eduPurpose: Black raspberries (BRBs) and their anthocyanin-rich hydrophilic fractions (BRB-H) have exhibited significant chemopreventative activity across aerodigestive cancers. Lutein, the primary component of the BRB lipophilic fraction (BRB-L), also demonstrates bioactivity potential, but is less well characterized, in part because of its poor, innate bioavailability. For these lipophilic compounds to be accurately evaluated for anticancer efficacy, it is necessary to increase their functional bioavailability using delivery vehicles. Lutein has been delivered in commercial settings in emulsion form. However, emulsions are unstable, particularly in the gastrointestinal tract, which limit their use as an oral nutraceutical. Here, we evaluated lutein encapsulation and cellular uptake for nanoparticle (NP) delivery vehicles composed of three different materials synthesized via two different approaches.Methods: Specifically, NPs were synthesized via smaller scale batch interfacial instability (II) sonication and semi-continuous high throughput electrohydrodynamic-mediated mixing nanoprecipitation (EM-NP) methods using polystyrene-polyethylene oxide (PSPEO) or polycaprolactone-polyethylene glycol (PCLPEG) block copolymers and PHOSPHOLIPON 90G® (P90G, Lipoid GmbH) lipids. Size distribution, lutein encapsulation efficiency (EE), and cellular uptake and delivery were evaluated for each NP formulation.Results: NPs produced via high throughput EM-NP had higher EEs than NPs produced via batch II sonication, and P90G had the greatest EE (55%) and elicited faster cellular uptake in premalignant oral epithelial cells (SCC83) compared to other delivery systems.Conclusion: These qualities suggest P90G could be a beneficial candidate for future lutein in vitro delivery research and clinical translation for oral cancer prevention.Keywords: black raspberries, lutein, oral cancer, scalable nanomanufacturing, nanoprecipitation, emulsification